2020
DOI: 10.1016/j.bbi.2020.04.040
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nutrition on COVID-19 susceptibility and long-term consequences

Abstract: While all groups are affected by the COVID-19 pandemic, the elderly, underrepresented minorities, and those with underlying medical conditions are at the greatest risk. The high rate of consumption of diets high in saturated fats, sugars, and refined carbohydrates (collectively called Western diet, WD) worldwide, contribute to the prevalence of obesity and type II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
463
0
45

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(511 citation statements)
references
References 10 publications
(15 reference statements)
3
463
0
45
Order By: Relevance
“…In ammation is at the heart of the complications caused by this virus. In addition, it is good to remember that peripheral in ammation caused by COVID-19 can have long-term consequences that can lead to neurodegenerative dementia and disease through neuroin ammatory mechanisms that can be potentiated and aggravated by an unhealthy diet, especially in the most vulnerable people [60]. In addition to investing in healthy foods, we have to restrict in ammatory foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ammation is at the heart of the complications caused by this virus. In addition, it is good to remember that peripheral in ammation caused by COVID-19 can have long-term consequences that can lead to neurodegenerative dementia and disease through neuroin ammatory mechanisms that can be potentiated and aggravated by an unhealthy diet, especially in the most vulnerable people [60]. In addition to investing in healthy foods, we have to restrict in ammatory foods.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of a western type diet activates the innate immune system and impairs adaptive immunity, leading to chronic in ammation, reducing the host's defences against COVID-19 [60]. It is also important to remember that the high rate of consumption of diets rich in saturated fats such as red meat, sugars and re ned carbohydrates worldwide, contributes to the prevalence of obesity and type 2 diabetes and can put these populations at increased risk for developing severe COVID-19 and lead to higher mortality [60]. At the moment when we are going through this pandemic, it is essential to consider the impact of lifestyle habits, such as the consumption of unhealthy diets, on susceptibility to COVID-19 as well as on its recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connection between socio-cultures, climate change, humidity and seasonal variability assume that the risk of transmission of SARS-CoV-2 does appear to be the greatest [43,44]. Additionally, variation in food availability and food intake, age, and sex are important factors which could also play a role in the SARS-CoV-2 noti cation variability [45]. Ethnicity is another key player for increased risk of acquiring SARS-CoV-2 infection, for instance, studies have revealed that the Black, Asian and Minority Ethnic individuals are more prone and worsen clinical complications from COVID-19 compared to White individuals [46][47][48].…”
Section: Identi Cation Of the Key Medical And Social Elementsmentioning
confidence: 99%
“…Therefore, we can guess that the above factors may be closely related to COVID-19. It is gratifying that recently some prospective studies [17][18][19] provide an association between factors (age, basic health situation, and virus transmission speed) and mortality of COVID-19. However, to our best knowledge, some relationship between environmental factors, including meteorological factors and the death risk of COVID-19 patients remain unknown, might need further investigation.…”
Section: Introductionmentioning
confidence: 99%